Low-Hemoglobin Levels During Pregnancy with Low-Birth Weight: A Systematic Review and Meta-Analysis - Lucyana Septia Pramita; Widati Fatmaningrum; Martono Tri Utomo; Muhammad Ilham Aldika Akbar (Pediomaternal Nursing Journal, 2021)
Introduction: Low birth weight (LBW)  is one of the main risk factors for neonatal morbidity and mortality. Anemia in developing countries is still quite high compared to developed countries. Low hemoglobin levels in pregnancy can affect the birth of low birth weight babies.Methods: This study used a systematic review method. Studies published between 2015 and 2019. Search for articles was reviewed systematically through Scopus, ScienceDirect, Cochrane, and PubMed databases. The final results obtained 10 articles following the inclusion and exclusion criteria. Calculation result using Meta-Analysis with help of Comprehensive Meta-Analysis (CMA) software.Results: Compare the odds ratio and confidence interval of hemoglobin levels compared to low birth weight events. The results obtained OR 1.449 (95% CI 0.964 – 2.177) and p-Value 0.074 so that there is no relationship of hemoglobin levels in pregnant women ≤ 11gr / dL with the incidence of low birth weight babies. In the heterogeneity test results, I-Squared results obtained by 79.191%, which indicates the value of I-squared heterogeneity> 50% so that the sample used is heterogeneous. Maternal age less than 20 years or more than 35 years, number of parity, pregnancy spacing, and number of problems in the assessment of pregnancy and previous labor.Conclusion: There is no correlation between low maternal hemoglobin levels with the incidence of low birth weight because there are other factors that can affect outcomes such as different respondent characteristics, number of samples, different research countries, different trimester of pregnancy and other factors that can cause research bias.